Study of apolipoprotein C3 S1/S2 (C3238G, rs5128) polymorphism in Caucasian population of Eastern Siberia - O. V. Kalyuzhnaya; T. A. Bairova; V. V. Dolgikh; S. I. Kolesnikov (Acta Biomedica Scientifica, 2014)
The prevalence of genotypes and alleles of polymorphic marker S1 /S2 Apolipoprotein C3 in healthy adolescent Caucasians (Russians) living in Eastern Siberia was studied. Material for research was the DNA extracted from the venous blood; genotype was determined by PCR-RFLP for each sample. In the studied sample in 88.9 % of cases genotype S1/ S1 was detected, genotype S1/S2 was found in 8.6 %, S2/S2 - in 2.5 %. The share of S2 allele was 6.8 %, which is not significantly different from the previously studied Caucasoid populations.